Comparing the Employment-Output Elasticities of Expatriates and Nationals in the Gulf Cooperation Council - Behar, Alberto (IMF Working Papers; Working Paper ;, 2015)
We estimate the elasticity of private-sector employment to non-oil GDP in the Gulf Cooperation Council (GCC) for GCC nationals and expatriates using a Seemingly Unrelated Error Correction (SUREC) model. Our results indicate that the employment response is lower for nationals, who have an estimated short-run elasticity of only 0.15 and a long-run response of 0.7 or less. The elasticity is almost unity for expatriates in the long run and 0.35 in the short run. We interpret low elasticities as indirect evidence of labor market adjustment costs, which could include hiring and firing rigidities, skills mismatches, and reluctance to accept private sector jobs. Forecasts suggest that, absent measures to reduce adjustment costs, the private sector will only be able to absorb a small portion of nationals entering the labor force.